2013
DOI: 10.1111/ans.12096
|View full text |Cite
|
Sign up to set email alerts
|

Smokers know little of their increased surgical risks and may quit on surgical advice

Abstract: Background: Smoking cessation before surgery improves perioperative outcomes and some smokers may quit if undergoing surgery. Quitting smoking in community settings is influenced by physician quit advice and knowledge of smoking hazards, but there are few data on whether this applies in perioperative settings. Method: Survey on day of surgery of elective patients who reported being a smoker at the time of wait-list placement. Duration of smoking abstinence before surgery (if any) and length timing of failed qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
1
32
1
Order By: Relevance
“…The benefits of stopping smoking before surgery are substantially different, and may be realized sooner, than the benefits from smoking cessation in patients who are not scheduled to have operations. Surveys of smokers' knowledge suggest that they are aware of the general health risks of smoking, but under-appreciate that there are specific peri-operative risks (Webb et al, 2013; Bottorff et al, 2015). However, when controlling for other BCTs which were often delivered alongside BM1, the effects drifted to non-significance.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of stopping smoking before surgery are substantially different, and may be realized sooner, than the benefits from smoking cessation in patients who are not scheduled to have operations. Surveys of smokers' knowledge suggest that they are aware of the general health risks of smoking, but under-appreciate that there are specific peri-operative risks (Webb et al, 2013; Bottorff et al, 2015). However, when controlling for other BCTs which were often delivered alongside BM1, the effects drifted to non-significance.…”
Section: Discussionmentioning
confidence: 99%
“…10 Concerns that perioperative abstinence will exacerbate psychological stress or that patients will be offended if clinicians address their tobacco use are baseless. [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] What implementation process should be followed? Although descriptions of tobacco treatment implementation in clinical settings are available, none has been evaluated within an implementation science framework.…”
Section: Fig 4 | Consolidated Framework For Implementation Research-cmentioning
confidence: 99%
“…It has been suggested that the pre‐operative visit and peri‐operative period are an opportunity for a ‘teachable moment’ for smoking cessation interventions . Many smokers are not aware that smoking increases their risks of anaesthetic and surgical complications . When smokers were educated about the increased risks of postoperative complications, they were more likely to attempt to quit (Raveendran R, Islam S, Chung F, Wong J.…”
Section: Surgery As a Teachable Momentmentioning
confidence: 99%